Non-communicable diseases in the world over the past century: a secondary data analysis - Taheri Soodejani, Moslem (Frontiers in Public Health, 2024)
Introduction We analyzed the changes in the top 10 non-communicable diseases (NCDs) over the past century across the World Health Organization (WHO) regions. Materials and methods The data were extracted from the Global Burden of Disease (GBD) studies. After we accessed this source, all NCDs were sorted according to their prevalence in 2019, and the 10 most common NCDs were selected. Then, the incidence, prevalence, and mortality rates of these 10 NCDs were compared to the rates in 2000. Results Diabetes and kidney disease had the highest increase in incidence (49.4%) and prevalence (28%) in the Eastern Mediterranean region. Substance use disorders had a huge increase (138%) in the mortality rates among women in the Americas region. On the other hand, women in Southeast Asia experienced the greatest decrease in incidence (−19.8%), prevalence (−15.8%), and mortality rates (−66%). Conclusion In recent years, nearly all NCDs have shown an increase, yet mortality rates have declined across all regions. Lifestyle can be a major cause of this increase, but advancements in health and medical services, such as screening and treatment, have played a crucial role in improving survival rates.